1995
DOI: 10.1074/jbc.270.40.23546
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Oocytes and Somatic Cells Express Different Splice Variants of a Multifunctional Receptor

Abstract: An abundant 95-kDa protein belonging to the low density lipoprotein receptor supergene family is essential for chicken oocyte growth by mediating the uptake of multiple plasma-borne yolk precursors. This receptor harbors at the amino terminus a cluster of eight tandemly arranged repeats typical of the ligand binding domains of members of this family and is designated low density lipoprotein receptor relative with 8 repeats (LR8). Here, we demonstrate by reverse transcriptasepolymerase chain reaction, Northern,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 51 publications
2
91
0
Order By: Relevance
“…As described in numerous publications, VLDLR is massively expressed by growing oocytes and mediates the transport of VLDL, VTG, and other minor yolk components from the circulation into the growing germ cell (31). Earlier studies have demonstrated that granulosa cells express a splice variant of VLDLR that differs from the variant expressed in the oocyte by the presence of the O-linked sugar domain of the receptor (VLDLRϩ) (13). Here ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in numerous publications, VLDLR is massively expressed by growing oocytes and mediates the transport of VLDL, VTG, and other minor yolk components from the circulation into the growing germ cell (31). Earlier studies have demonstrated that granulosa cells express a splice variant of VLDLR that differs from the variant expressed in the oocyte by the presence of the O-linked sugar domain of the receptor (VLDLRϩ) (13). Here ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, ApoER2 has been shown to be preferentially expressed in bovine dominant follicles when compared with subordinate follicles (12). A splice variant of VLDLR, which is the major player in yolk uptake by the oocyte, is also expressed in chicken granulosa cells (13).…”
mentioning
confidence: 99%
“…In Situ Hybridization-Tissue sections from ovarian follicles (small yellow, 5-6 mm in diameter) were prepared for in situ hybridization as described earlier (25,26). The sections (8 m) were hybridized overnight at 45°C with prehybridization solution containing 10% dextran sulfate and ϳ300 pg/l of the digoxigenin-labeled antisense or sense RNA probes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, two oocyte-specific LDLR family members have been described. One is the chicken homologue of the mammalian so-called VLDL receptor, termed LR8 for its harboring 8 LDL receptor ligand binding repeats, that serves as a receptor for a broad spectrum of ligands (19,25). The other receptor is an LDL receptor-related protein (LRP) with an apparent M r of ϳ380,000 (28), here termed LRP380.…”
Section: Figmentioning
confidence: 99%
“…Chicken oocytes and somatic cells express different splice variants of VLDLR (Bujo et al 1995). There have been no reports about the expression of the two VLDLR subtypes in waterfowl.…”
mentioning
confidence: 99%